EXPLORING THE ROLE OF UNIVERSITY STUDENTS’ ONLINE SELF-REGULATED LEARNING ACROSS DIFFERENT EPISTEMIC BELIEFS LEVELS - stephani wulandari tasik (EDUCAFL : Journal of Education of English as Foreign Language, 2020)
Self-regulated learning is one of the keys of success in acquiring knowledge. Epistemic beliefs also play an important role on the self-regulated learning process. It affects students’ achievements depend on each belief of knowledge and knowing. However, less attention given to the constructs on online learning environment. The main purpose of this research was to know the extent of EFL students’ Online Self-regulated English Learning (OSEL) across the different level of Epistemic Beliefs. A total of 100 EFL students from Universitas Brawijaya were chosen randomly as the samples for this study. This survey study was adopting two questionnaires from Emaliana (2017) and Zheng et al. (2016) to gather the data. The result reports that there were from 81 students who have sophisticated epistemic beliefs, 54 students are having Advanced OSEL. It indicated that the extent of EFL students’ OSEL across different epistemic beliefs levels are great. Unexpectedly, it was found that there are students who have Basic OSEL with sophisticated epistemic beliefs and vice versa. Accordingly, it is recommended for further researcher to investigate this unique case. By using a qualitative design, it might enable further researchers to get profound result.